Fat Emboli with Thrombocytopenia in A Patient Undergoing Operation for A 1/3 Medial Humerus Oblique Fracture - Ardianto, Son; Alexander, Devin; Wahono, Budi (International Journal of Public Health Excellence (IJPHE), 2024)
Fat embolism is a clinical syndrome characterized by the systemic spread of fat emboli which often occurs due to fractures in long bones. We report a 29 year old man with a diagnosis of a fracture of the medial third of the right humerus accompanied by thrombocytopenia which could be one of the clinical manifestations of pulmonary embolism. A 29 year old man came to the emergency room at RAA Soewondo Pati Regional Hospital with complaints of pain in his right hand 2 hours before entering the hospital. The patient felt pain after falling and slipping at home. Physical examination revealed tachycardia and tachypnea. Humeral x-ray revealed discontinuity in the medial 1/3 of the right humerus. The patient then underwent treatment for the fracture and the day after a routine blood test was carried out. Routine blood tests revealed thrombocytopenia.Fat embolism is a dangerous complication of long bone fractures. Often this fat embolism is not recognized until the patient shows symptoms in several systems, especially the respiratory system such as respiratory distress and neurological system disorders ranging from motor disorders to seizures. Apart from that, fat embolism can also disrupt the coagulation system so that thrombocytopenia can occur. In this patient there was tachypnea and thrombocytopenia which could be early symptoms of fat embolism. Fat embolism is a complication of long bone fractures that is rare but dangerous if not properly recognized. Immediate management of fractures and collaboration with anesthesiologists and internists are important to prevent fat embolism.